STABILITY OF NON-SURFACTANT WATER AND HYDROGEN PEROXIDE EMULSIONS IN B0 AND B35 USING INLINE MIXER - Muhammad Fariedz Irawan; Frendy Rian Saputro; Dhani Avianto Sugeng; Agus Mulyana; Kurnia Fajar Adhi Sukra; Fakhrul Afif Uzair; Wira Jazair Yahya; Rizqon Fajar; Boni Sena; Ujiburrahman Ujiburrahman (Scientific Journal of Mechanical Engineering Kinematika, 2026)
Hydrogen peroxide (H2O2) enrichment is known to enhance combustion efficiency in diesel engines; however, its application as an emulsion is restricted by phase instability in the absence of chemical surfactants. This study investigates the stability and temperature characteristics of non-surfactant emulsions produced using an inline mixer known as the Real-Time Emulsion Supply System (RTES). Four emulsion types were formulated using water and aqueous H2O2 (5-15 vol%) as the dispersed phase, with neat diesel (B0) and biodiesel (B35) serving as the continuous phase: water-in-B0 (WD), H2O2-in-B0 (HD), water-in-B35 (WB), and H2O2-in-B35 (HB). The emulsions were prepared using RTES with a residence time of 180 s. During the preparation, the temperature was continuously recorded using a Graphtec GL840 data logger. The phase separation was monitored over 600 s using a Canon-EM3 camera. Results demonstrate that B35-based emulsions exhibit higher stability compared to B0-based emulsions. The stability tests showed distinct phase separation ratios for each formulation: 12.67% for WD, 10.67% for HD, 4.67% for WB, and 4.27% for HB. Meanwhile, the temperature rise (ΔT) varied slightly by formulation, ranging from 1.67-1.97 °C for WD and HD, and from 2.33-2.73 °C for WB and HB.